The importance of Ria de Aveiro’s saltpans during winter for migratory - Gomes, Liliana Medeiros (2018)
Intertidal wetlands are among the most productive habitats and support large numbers of waterbirds worldwide, however they are also one the most threatened habitats on the planet. The loss of intertidal habitats is considered a key factor in explaining the current decline of many waterbird populations. Anthropogenic supratidal habitats such as coastal saltpans can operate as buffer zones against the loss of natural coastal habitats. Therefore, saltpan abandonment can lead to a loss of the quality of these areas for waders. This study aimed to evaluate the implications that the current trend of traditional salt works abandonment can have on wader populations. Wader surveys were undertaken in saltpan tanks currently under one of 3 different regimes – active saltpans, active aquaculture and inactive/shattered – during both high tide and low tide between October 2014 and March 2015. The observations showed that a larger number of wintering waders use the active saltpans both during high and low tide. Nevertheless, the study of wader distribution in the different saltpans revealed differences between high tide and low tide. During rising tide, wader abundance significantly increases in active saltpans and aquaculture tanks and decreases in inactive tanks, whereas the opposite occurs during dropping tide. Active saltpans are an important feeding habitat for large waders, particularly for the black-winged stilt (Himantopus himantopus) and the black-tailed godwit (Limosa limosa), in both high tide and low tide. These results highlight the importance of artificial habitats such as active saltpans for wintering waders and the value of its correct management towards the conservation of waders in Ria de Aveiro.